2022
DOI: 10.1007/s10877-022-00878-2
|View full text |Cite
|
Sign up to set email alerts
|

Intra-abdominal hypertension in cardiac surgery patients: a multicenter observational sub-study of the Accuryn registry

Abstract: Intra-abdominal hypertension (IAH) is frequently present in the critically ill and is associated with increased morbidity and mortality. Conventionally, intermittent ‘spot-check’ manual measurements of bladder pressure in those perceived as high risk are used as surrogates for intra-abdominal pressure (IAP). True patterns of IAH remain unknown. We explored the incidence of IAH in cardiac surgery patients and describe the intra-and postoperative course of IAP using a novel, high frequency, automated bladder pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…The use of continuous IAP monitoring will, in the future, likely detect higher rates of IAH and has many benefits beyond that are detailed elsewhere [41]. This is exemplified by the recent finding that IAH detected by continuous IAP monitoring in cardiac surgery patients was above 90% in the first 48 hours after surgery [42].…”
Section: Vre Vancomycin Resistant Enterococcusmentioning
confidence: 99%
“…The use of continuous IAP monitoring will, in the future, likely detect higher rates of IAH and has many benefits beyond that are detailed elsewhere [41]. This is exemplified by the recent finding that IAH detected by continuous IAP monitoring in cardiac surgery patients was above 90% in the first 48 hours after surgery [42].…”
Section: Vre Vancomycin Resistant Enterococcusmentioning
confidence: 99%
“…Recently, the Accuryn Monitoring System (Potrero Medical, Hayward, California, USA) using a special urinary catheter with an extra air-filled balloon at the tip has been FDA cleared for measuring IAP, urinary output (UO), and core body temperature. A significant advantage of this system is near-continuous, high-fidelity and high-resolution IAP monitoring as shown in a recent study in cardiac surgery patients observing persistent increases in IAP that had previously not been shown with traditional spot-check measurements [ 10 ]. One more consideration when measuring IAP at high frequency is the signal to noise factor.…”
Section: Continuous Intra-abdominal Pressure Measurementmentioning
confidence: 99%
“…One more consideration when measuring IAP at high frequency is the signal to noise factor. Applying a 10-min running median and resampling data at longer intervals every 15 min may help mitigate the effect of patient position and factors that induce rapid sudden changes in IAP such as diaphragmatic contraction with a coughing [ 10 ].…”
Section: Continuous Intra-abdominal Pressure Measurementmentioning
confidence: 99%
“…Although some studies show a lower incidence of ACS (approximately 3–5%) in general ICU patients [ 7 ], the risk of ACS in critically ill patients should not be underestimated. For instance, a recent study that included 138 post-cardiac surgery patients showed an IAH occurrence rate of 100% during the first 24 h post-operatively, with a sustained IAP pressure above 20 mmHg for approximately 5 h [ 8 ]. Therefore, continuous IAP monitoring is of great importance to prevent late detection of IAH, development of ACS, and potentially contribute to a reduced length of ICU stay.…”
Section: Introductionmentioning
confidence: 99%